From Power To Persecution: The Fate Of Sultan Alauddin Muhammad - Primov Mukhiddinjon Omonovich; Qiranova Chehrona Dilshod qizi (Periodica Journal, 2025)
This article analyzes the political activities, personality, military successes, and tragic end of Sultan Alauddin Muhammad, the last powerful representative of the Khwarazmshah dynasty. Based on historical sources, it is described how he was expelled from his homeland before the Mongol invasion and spent his final days on the island of Ashura. The influence of world instability and historical changes is shown through the Sultan's need for a single horse from a powerful empire. The article illuminates the image of a historical figure from a human and political point of view, and also provides information about the fate of his family members
Keywords: Khwarazmian Empire; Ala ad-Din Muhammad; Abeskun Island